Beispiel Nr: 62
$ \text{Gegeben:} y=ax^2+bx+c \\ \text{Gesucht:} \\ \text{Scheitel und Scheitelform}\\ \text{Definitions- und Wertebereich} \\ \text{Nullstellen - Schnittpunkt mit der x-Achse} \\ \text{Faktorisiere Form} \\ \text{Scheitel} \\ Eigenschaften\\ \textbf{Gegeben:} \\ y=-2x^2+3x+4\\ \\ \textbf{Rechnung:} \\\bullet \text{Funktion} \\ y=-2x^2+3x+4\\ \\ \bullet \text{Scheitelberechnung } \\ \begin{array}{l|l|l} \begin{array}{l} \text{quadratische Ergänzung } \\ \hline y=-2x^2+3x+4 \\ y=-2(x^2-1\frac{1}{2}x-2) \\ y=-2(x^2-1\frac{1}{2}x+\left(\frac{3}{4}\right)^2-\left(\frac{3}{4}\right)^2-2) \\ y=-2[(x-\frac{3}{4})^2-\left(\frac{3}{4}\right)^2-2] \\ y=-2[(x-\frac{3}{4})^2-\frac{9}{16}-2] \\ y=-2[(x-\frac{3}{4})^2-2\frac{9}{16}] \\ y=-2(x-\frac{3}{4})^2+5\frac{1}{8} \\ Scheitel(\frac{3}{4}/5\frac{1}{8}) \end{array} & \begin{array}{l} \text{quadratische Ergänzung } \\ \hline y=-2x^2+3x+4 \\ y=-2(x^2-1\frac{1}{2}x)+4 \\ y=-2(x^2-1\frac{1}{2}x+\left(\frac{3}{4}\right)^2-\left(\frac{3}{4}\right)^2)+4 \\ y=-2[(x-\frac{3}{4})^2-\left(\frac{3}{4}\right)^2]+4 \\ y=-2[(x-\frac{3}{4})^2-\frac{9}{16}]+4 \\ y=-2(x-\frac{3}{4})^2+1\frac{1}{8}+4 \\ y=-2(x-\frac{3}{4})^2+5\frac{1}{8} \\ Scheitel(\frac{3}{4}/5\frac{1}{8}) \end{array} & \begin{array}{l} \text{Scheitelformel} \\ \hline y=-2x^2+3x+4 \\ xs=-\frac{3}{2\cdot \left(-2\right)} \\ xs=\frac{3}{4} \\ ys=4-\frac{3^2}{4\cdot\left(-2\right)} \\ ys=5\frac{1}{8} \\ Scheitel(\frac{3}{4}/5\frac{1}{8})\\ y=-2(x-\frac{3}{4})^2+5\frac{1}{8} \end{array} \\ \end{array} \\ \\ \\\bullet\text{Definitions- und Wertebereich:}\qquad \mathbb{D} = \mathbb{R} \qquad \mathbb{W} = ]-\infty;5\frac{1}{8}]\\ \\=-2(x+0,851)(x-2,35)\\ \\\bullet \text{Nullstellen / Schnittpunkt mit der x-Achse:} \\y=-2x^2+3x+4 = 0 \\ \begin{array}{l|l|l} \begin{array}{l} \text{a-b-c Formel}\\ \hline \\ -2x^{2}+3x+4 =0 \\ x_{1/2}=\displaystyle\frac{-3 \pm\sqrt{3^{2}-4\cdot \left(-2\right) \cdot 4}}{2\cdot\left(-2\right)} \\ x_{1/2}=\displaystyle \frac{-3 \pm\sqrt{41}}{-4} \\ x_{1/2}=\displaystyle \frac{-3 \pm6,4}{-4} \\ x_{1}=\displaystyle \frac{-3 +6,4}{-4} \qquad x_{2}=\displaystyle \frac{-3 -6,4}{-4} \\ x_{1}=-0,851 \qquad x_{2}=2,35 \end{array}& \begin{array}{l} \text{p-q Formel}\\ \hline \\ -2x^{2}+3x+4 =0 \qquad /:-2 \\ x^{2}-1\frac{1}{2}x-2 =0 \\ x_{1/2}=\displaystyle -\frac{-1\frac{1}{2}}{2}\pm\sqrt{\left(\frac{\left(-1\frac{1}{2}\right)}{2}\right)^2- \left(-2\right)} \\ x_{1/2}=\displaystyle \frac{3}{4}\pm\sqrt{2\frac{9}{16}} \\ x_{1/2}=\displaystyle \frac{3}{4}\pm1,6 \\ x_{1}=2,35 \qquad x_{2}=-0,851 \end{array}\\ \end{array}\\ \underline{x_1=-0,851; \quad1\text{-fache Nullstelle}} \\\underline{x_2=2,35; \quad1\text{-fache Nullstelle}} \\ \\ \bullet \text{Vorzeichentabelle:} \\ \begin{array}{|c|c|c|c|c|c|c||} \hline & x < &-0,851&< x <&2,35&< x\\ \hline f(x)&-&0&+&0&-\\ \hline \end{array}\\ \\ \underline{\quad x \in ]-0,851;2,35[\quad f(x)>0 \quad \text{oberhalb der x-Achse}}\\ \\ \underline{\quad x \in ]-\infty;-0,851[\quad \cup \quad]2,35;\infty[\quad f(x)<0 \quad \text{unterhalb der x-Achse}}$